IMPROVING THE STUDENTS READING SKILL IN FINDING OUT MAIN IDEA BY USING PARAGRAPH PATTERN (ELang | An English Language Education Journal, 2019)
title of the research paper was “Improving the students reading skill in finding out the main idea by using paragraph pattern “is submitted to the English Educational study Program of the Faculty of Teachers Training and Educational Sciences of Bale Bandung University as partial fulfillment of the requirements for taking Sarjana Pendidikan degree. The aims of the study are to know the effectiveness of paragraph pattern in improving reading skill to the nine grade of SMP PEMUDA BANJARAN and also to know students’ responses toward the use of Paragraph pattern in teaching reading. In doing the research, the study use a pre-experimental research. The sample of the research are 25 students of SMP PEMUDA BANJARAN. The instruments are pre-test, post-test and questionnaire. The pre-test was given to know how far the students’knowledge and scores before they were given the treatments. And the post-test was given to get the students’ score after the treatments. And then, questionnaire was given to know the students’ responses of using paragraph pattern in teaching reading. The result of the research after calculating the data is with df 25, t-table at the level of significance of .05 for two tailed is 2.064. As to bigger than t-table ( 4.57 > 2.064 ) Ho is rejected and Ha is accepted. Therefore, this means that this technique is effective. Besides that from the result of questionnaire, the writer can conclude that the students’ responses toward in finding out the main idea by using paragraph pattern in teaching reading is positive. It means that they can improve their ability especially in teaching reading paragraph pattern technique.Keywords : Paragraph patt